Quality of life and its relationship to achievement motivation among high school students in Kingdom of Saudi Arabia- Asir region - Al Hader, Abdullah Saad (Journal of Educational and Psychological Sciences, 2021)
This research aimed at uncover the relationship between quality of life with its various dimensions and achievement motivation of students at the secondary level in the Asir region, as well as to identify the differences between students in both quality of life and achievement motivation in light of the area of ​​study (literary- scientific), and in light of the school year (second secondary- third- secondary), and to identify differences between the mean scores of students higher student achievement motivation and low achievement motivation in quality of life, and verification of predictability some dimensions of quality of life without other motivation achievement. Sample: The sample consisted of (500) students from the research community, including (250) students in Abha, and (250) Khamis Mushayt province. Research Methodology: The researcher using a linking descriptive method, comparative and descriptive method to verify the research hypotheses and answer his questions Tools: researcher used measure of the quality of life for (Thunayan, 2009), and the measure of achievement motivation (Khalifa, 2000). Results: The research found the following results: There is a positive correlation statistically significant (0.01) between each of the (quality of public health, and quality of family and social relationships, and the quality of mental health and feelings, and the quality of management time), and the dimensions of achievement motivation, and the overall degree of motivation achievement, while not Tugod correlation between after the quality of education, study and dimensions of achievement motivation, and the total score for the achievement motivation, as evidenced by the results of research on the presence of statistically significant differences at (0.05) among the students of the scientific section and section literary After the quality of education and the study and after planning for the future , and the total score for the achievement motivation, and when (0.01) after the pursuit of excellence for the benefit of students of scientific specialization, while there are no statistically significant differences in the rest of the dimensions of quality of life, and the total score for quality of life, as well as on the scope of the dimensions of achievement motivation of (feeling of responsibility, persistence, and orientation time), no statistically significant differences between the students of second grade students and third- grade secondary in all dimensions of quality of life and the total score, and also in the dimensions of driving achievement of (feeling of responsibility, and the pursuit of excellence, perseverance, and orientation time) , and the total score for the achievement motivation, while no statistically significant differences at (0.05) among the students of second grade secondary school students and third- grade secondary after planning the future for the benefit of students of second grade secondary education, there are differences between higher achievement motivation and low achievement motivation, in all dimensions of quality of life except after (the quality of education and study). And differences in the average was in favor of higher achievement motivation, droop some dimensions of quality of life motivation of achievement and of dimensions (quality of family and social relationships, the quality of mental health and feelings, the quality of public health, the quality of education and study), with a contribution of total (0.19).